Pengaruh Kualitas Produk, Harga dan Promosi Terhadap Keputusan Pembelian dengan Brand Image Sebagai Variable Moderating - Wellyn Sinta Maria Purba; Syahfirin Abdullah; Edison Cholia Sembiring (CV. Syntax Corporation Indonesia, 2021)
The development of industries engaged in personal care is increasing rapidly. This is how we see from the level of demand for dating treatment is increasing. Anti-aging products, one of which is Pond's Age Miracle is one of the products sought by especially women where this product is one of the number one anti-aging products in Indonesia where it always innovates its products. The purpose of this study was to test the influence of factors such as product quality, price, and promotion of purchase decisions with brand image as variable moderating in Pond's Age Miracle products. This study was obtained through filling out questionnaires with a sample of 12o respondents with purposive sampling criteria, and then tested to measure consumer perception through the SEM model with PLS. Test results from this study showed that purchasing decisions were significantly influenced by product quality and price factors but not by promotion. In addition, the results also showed that brand image was able to moderate the influence of product quality, price, and promotion on Pond's Age Miracle product purchase decisions